Ethnic And Cultural Diversity of Indonesia with Project-Based Learning in Elementary School - Yanti Sudiarti; Armani Armani; Rahmawati Rahmawati (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2023)
This study discusses improving students' knowledge and understanding of Indonesia's diversity of ethnicities and cultures using the project-based learning (PjBL) model. Each individual or group does not know precisely where the material will be given when starting the learning process. This study used PjBL model with a quantitative descriptive research approach. Classroom Action Research (CAR) is a way of determining how to do it with cycle I and II. There were 27 students in the fifth grade at State Elementary School participated in this study. Cycle 1 passed 20 students with a percentage of 74% and those who have not passed were 7 students with a percentage of 26%. In cycle II with improved planning and implementation 27 students passed with a Percentage of 100%. The existence of the PjBL Model, understanding of the Diversity of Indonesian Ethnicity and Culture in social studies learning can be accepted because of the concentration in the direct trial process and one of the students is given a wide opportunity to conduct a smaller and effective discussion. If there is difficulty for students during learning, they can provide information to each other through questions and answers and look for references in learning books.